PHYGITAL EXPERIENCE IN E-AUCTION SERVICES: A SYSTEMATIC REVIEW OF THE LITERATURE ON ITS EFFECTS ON CITIZEN SATISFACTION, TRUST, AND PARTICIPATION INTENTION - Deny Ariyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study conducts a Systematic Literature Review (SLR) to synthesize current evidence on phygital experience, defined as the integration of physical and digital channels, in public e-auction services managed by the Directorate General of State Assets (DJKN). A structured search was performed through the Scopus database for publications between 2010 and 2024, using Boolean-based keywords related to phygital services, hybrid public service delivery, digital government, citizen satisfaction, trust, and participation intention. The review followed PRISMA 2020 procedures, resulting in the identification of 10 eligible studies out of the initial screening. The findings show that phygital experience improves transparency, accessibility, service reliability, and perceived fairness, which in turn significantly enhance citizen satisfaction, institutional trust, and participation intention in digital public services. Despite these positive outcomes, the literature reveals several gaps, including the lack of longitudinal evidence, limited focus on digital inclusivity, and inconsistent conceptual definitions of phygital experience. This study contributes by providing a synthesized conceptual understanding of phygital experience in the public sector, especially in high-stakes services such as e-auction. The results offer strategic guidance for designing more user-centered, inclusive, and trustworthy hybrid service models.